2013
DOI: 10.12816/0006017
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Density in Oral Submucous Fibrosis : A Possible Role in Pathogenesis

Abstract: Abstract:Objective: Oral submucous fibrosis (OSMF) is a premalignant condition of oral cavity characterized by inflammation and progressive mucosal fibrosis. It has questionable pathogenesis. Mast cells (MC) have been associated with variety of inflammatory and fibrotic conditions, but little is known about their role in OSMF. Mast cells have been studied in normal gingiva, chronic inflammatory gingivitis, desquamative gingivitis, lichen planus, OSMF and oral cancer. Mast cells exhibit phenotypic plasticity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 11 publications
1
17
1
2
Order By: Relevance
“…The present study demonstrated a significantly higher subepithelial distribution of tryptase positive MCs than chymase positive MCs in the early stages of OSF against the increased distribution of tryptase positive MCs than chymase positive MCs in deeper zones of the advanced stages of OSF, which was in accordance with other findings in the literature [13], [14], [15], [16], [17], [18], [19]. This trend of initial increase in number of MC in stage I OSF followed by subsequent decrease in number of MC in later stages of OSF could be attributed to the initial inflammatory response of oral mucosa to the exogenous irritants and carcinogens like areca nut and tobacco.…”
Section: Discussionsupporting
confidence: 93%
“…The present study demonstrated a significantly higher subepithelial distribution of tryptase positive MCs than chymase positive MCs in the early stages of OSF against the increased distribution of tryptase positive MCs than chymase positive MCs in deeper zones of the advanced stages of OSF, which was in accordance with other findings in the literature [13], [14], [15], [16], [17], [18], [19]. This trend of initial increase in number of MC in stage I OSF followed by subsequent decrease in number of MC in later stages of OSF could be attributed to the initial inflammatory response of oral mucosa to the exogenous irritants and carcinogens like areca nut and tobacco.…”
Section: Discussionsupporting
confidence: 93%
“…The habit of tobacco consumption is a known etiological factor for the development of precancerous diseases and oral cancer. 6,7,8 Cancer of the oral cavity constitutes about 3-4% of all cancers in western industrialized countries, mainly affects middle aged people, and is more common in men than in women. In India where the habits of chewing tobacco with betel nut, reverse smoking and alcohol usage are common, there is a striking incidence of oral cancer which accounts for as many as 30-40% of all cancers.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a study has shown that there is no significant increase among well, moderate, or poorly differentiated squamous cell carcinoma [49]. The mast cell population is significantly increased in advanced stages of epithelial dysplasia and oral submucous fibrosis [55]. A molecular epidemiological study on mast cell population revealed a significantly higher number of mast cells in squamous cell carcinoma of skin than oral mucosa.…”
Section: Evidence-based Report On the Role Of Mast Cells In Oral Squamentioning
confidence: 99%